Relationship Between Awareness of HIV/AIDS and Attitudes of Secondary School Students to Premarital HIV Counseling and Testing in Zaria, Northern Nigeria - OR Obiako; HM Muktar; TL Sheikh; AI Mamman; Anyebe EE; Obiako CO (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Background: In Nigeria HIV infection is transmitted mainly through heterosexual route, affecting mostly individuals within reproductive age groups. As a result, HIV/AIDS education is advocated as a strong component of family and reproductive health education in the school curriculum which should emphasize responsible sexual behavior, premarital chastity and protective sexual practice. Aims/ Objectives: To evaluate student’s knowledge of HIV/AIDS, premarital HCT, and reactions to possible discordant HCT results. Methods: Cross sectional questionnaire-based study of 600 students in 6 schools in Zaria/Sabon Gari LGAs. Exclusion criteria: students aged ≤13 years, married, in JSS 1-3, SS1. Results: 550 students completed questionnaire (92% response rate). 54.5% females (ᾱ age =17.5 ±2.7 years) versus 45.5% males (16.5 ±2.7 years), Muslims (53%) and Christians (47%) respectively. 76%, 57%, and 38% knew the meaning of AIDS, HIV and VCT respectively; while all knew both the routes of HIV transmission and preventive measures. More than two-third supported voluntary, free and self initiated premarital HCT, preferably in a private and confidential setting. None would marry a discordant HIV positive partner, while 61% would marry themselves if both have positive HIV results. Conclusion: Many students would shun marriage with discordant HIV+ partner.
Keywords: Pre-marital